A Symmetrical Three-Phase AC-AC Converter Designed by Using Switched-Capacitor Techniques - Kei Eguchi; Kanji Abe; Sawai Pongswatd; Prasit Julsereewong; Amphawan Julsereewong; Ichirou Oota (My University, 2016)
In the field of power engineering, a three-phase transformer is widely used to provide the load with sinusoidal three-phase voltages. In this paper, a novel three-phase direct ac-ac converter is proposed for three-phase power conversion apparatus. The proposed ac-ac converter consists of three module blocks designed by switched-capacitor (SC) techniques, where each module block has symmetrical converter topology. Due to the symmetrical converter topology, the proposed ac-ac converter can realize not only high power efficiency but also high input power factor while keeping the frequencies of the input and output voltages equal. Furthermore, due to the inductor-less design, light weight and small converter size can be realized by the proposed SC ac-ac converter. Concerning the proposed ac-ac converter in the case of delta-wye, delta-delta, wye-delta and wye-wye connections, the operation principle, qualitative analysis and simulation evaluation are described. The results of the simulation program with integrated circuit emphasis (SPICE) simulation demonstrate the effectiveness of the proposed ac-ac converter.
Keywords: Three-phase; Advanced DC-DC Converters